Web design with HTML and CSS : digital classroom - Osborn, Jeremy; Smith, Jennifer (Digital classroom, 2011)
"Experts guide you through 12 lessons, helping you learn essential web design skills at your own speed. Full-color, step-by-step instructions in the book are enhanced with samples and materials on digitalclassroombooks.com. With Digital Classroom, you have your own private instructor showing you the easiest way to learn web design"-- Cover, p. [4]